Mosaic Activating Mutations in FGFR1 Cause Encephalocraniocutaneous Lipomatosis. - Bennett, James T; Tan, Tiong Yang; Alcantara, Diana; Tétrault, Martine; Timms, Andrew E; Jensen, Dana; Collins, Sarah; Nowaczyk, Malgorzata J M; Lindhurst, Marjorie J; Christensen, Katherine M; Braddock, Stephen R; Brandling-Bennett, Heather; et al. (Am J Hum Genet, 2016)
Encephalocraniocutaneous lipomatosis (ECCL) is a sporadic condition characterized by ocular, cutaneous, and central nervous system anomalies. Key clinical features include a well-demarcated hairless fatty nevus on the scalp, benign ocular tumors, and central nervous system lipomas. Seizures, spasticity, and intellectual disability can be present, although affected individuals without seizures and with normal intellect have also been reported. Given the patchy and asymmetric nature of the malformations, ECCL has been hypothesized to be due to a post-zygotic, mosaic mutation. Despite phenotypic overlap with several other disorders associated with mutations in the RAS-MAPK and PI3K-AKT pathways, the molecular etiology of ECCL remains unknown. Using exome sequencing of DNA from multiple affected tissues from five unrelated individuals with ECCL, we identified two mosaic mutations, c.1638C>A (p.Asn546Lys) and c.1966A>G (p.Lys656Glu) within the tyrosine kinase domain of FGFR1, in two affected individuals each. These two residues are the most commonly mutated residues in FGFR1 in human cancers and are associated primarily with CNS tumors. Targeted resequencing of FGFR1 in multiple tissues from an independent cohort of individuals with ECCL identified one additional individual with a c.1638C>A (p.Asn546Lys) mutation in FGFR1. Functional studies of ECCL fibroblast cell lines show increased levels of phosphorylated FGFRs and phosphorylated FRS2, a direct substrate of FGFR1, as well as constitutive activation of RAS-MAPK signaling. In addition to identifying the molecular etiology of ECCL, our results support the emerging overlap between mosaic developmental disorders and tumorigenesis.
Keywords: Adolescent; Cell Line, Tumor; Central Nervous System Neoplasms; Child, Preschool; Exome; Eye; Eye Diseases; Female; Humans; Infant; Lipomatosis; Male; Mutation; Mutation, Missense; Neurocutaneous Syndromes; Phosphatidylinositol 3-Kinases; Proto-Oncogene Proteins c-akt; Receptor, Fibroblast Growth Factor, Type 1; Seizures; Sequence Analysis, DNA

Structural variation and missense mutation in SBDS associated with Shwachman-Diamond syndrome. - Carvalho, Claudia M B; Zuccherato, Luciana W; Williams, Christopher L; Neill, Nicholas J; Murdock, David R; Bainbridge, Matthew; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; Ip, Wan; Guillerman, Robert Paul; Lupski, James R; et al. (BMC Med Genet, 2014)
BACKGROUND: Shwachman-Diamond syndrome (SDS) is an autosomal recessive ribosomopathy caused mainly by compound heterozygous mutations in SBDS. Structural variation (SV) involving the SBDS locus has been rarely reported in association with the disease. We aimed to determine whether an SV contributed to the pathogenesis of a case lacking biallelic SBDS point mutations. CASE PRESENTATION: Whole exome sequencing was performed in a patient with SDS lacking biallelic SBDS point mutations. Array comparative genomic hybridization and Southern blotting were used to seek SVs across the SBDS locus. Locus-specific polymerase chain reaction (PCR) encompassing flanking intronic sequence was also performed to investigate mutation within the locus. RNA expression and Western blotting were performed to analyze allele and protein expression. We found the child harbored a single missense mutation in SBDS (c.98A > C; p.K33T), inherited from the mother, and an SV in the SBDS locus, inherited from the father. The missense allele and SV segregated in accordance with Mendelian expectations for autosomal recessive SDS. Complementary DNA and western blotting analysis and locus specific PCR support the contention that the SV perturbed SBDS protein expression in the father and child. CONCLUSION: Our findings implicate genomic rearrangements in the pathogenesis of some cases of SDS and support patients lacking biallelic SBDS point mutations be tested for SV within the SBDS locus.
Keywords: Abdomen; Alleles; Bone Marrow Diseases; Cell Line, Transformed; Child, Preschool; Comparative Genomic Hybridization; DNA Mutational Analysis; Exocrine Pancreatic Insufficiency; Female; Gene Order; Humans; Lipomatosis; Mutagenesis, Insertional; Mutation; Mutation, Missense; Pedigree; Proteins; Radiography, Abdominal; Ultrasonography